2016
DOI: 10.1111/acem.13043
|View full text |Cite
|
Sign up to set email alerts
|

The Physician‐as‐Stakeholder: An Exploratory Qualitative Analysis of Physicians’ Motivations for Using Shared Decision Making in the Emergency Department

Abstract: Background: Shared decision making (SDM) is increasingly recognized as an important facet of patientcentered care. Despite growing interest in SDM in the emergency department (ED), little is known about emergency physicians' (EPs') motivations for using SDM. Understanding current patterns of SDM use and EP's rationale for using SDM is essential for the development of interventions to increase use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 24 publications
1
70
0
1
Order By: Relevance
“…21,22 To explore how the theory of planned behavior and social cognitive theory influence SDM, we conducted semistructured interviews with practicing EPs. We chose a purposeful sample of EM physicians based on sex, years in practice, region, employment setting (rural/suburban/urban), academic versus community practice setting, and location of training.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 To explore how the theory of planned behavior and social cognitive theory influence SDM, we conducted semistructured interviews with practicing EPs. We chose a purposeful sample of EM physicians based on sex, years in practice, region, employment setting (rural/suburban/urban), academic versus community practice setting, and location of training.…”
Section: Methodsmentioning
confidence: 99%
“…In our initial investigation of attending emergency physician (EP) attitudes and practices regarding their use of SDM, we discovered generally positive attitudes toward SDM, along with growing recognition of barriers to its routine use in the emergency department. 21 In this analysis, we examined emergency medicine (EM) faculty's experiences with acquisition of SDM skills and teaching these skills to residents. The goal was to improve our understanding of how clinicians acquire and teach SDM skills to facilitate and promote this patient-centered practice.…”
Section: Introductionmentioning
confidence: 99%
“…57 These studies have found that physicians often believe their patients do not want to be involved in decisions in the setting of emergency care. 5,6 However, no studies have examined SDM from the point of view of the ED patient.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency physicians’ (EPs’) perspectives on SDM have been evaluated by several surveys and qualitative studies . Although these studies did find that many EPs recognize the benefits of SDM and report using it frequently, numerous barriers were identified .…”
mentioning
confidence: 99%
“…Emergency physicians’ (EPs’) perspectives on SDM have been evaluated by several surveys and qualitative studies . Although these studies did find that many EPs recognize the benefits of SDM and report using it frequently, numerous barriers were identified . In a survey study by Kanzaria et al, physicians endorsed the following attitudes toward SDM in the emergency department (ED): 1) patients often preferred their doctors make decisions, 2) patients often opted for care deemed “more aggressive than needed” by physicians, 3) decisions were too complicated for patients, and 4) that SDM took too much time.…”
mentioning
confidence: 99%